Pengaruh Pelatihan Pasar Modal, Persepsi Risiko, Literasi Keuangan, Dan Modal Minimal Investasi Terhadap Minat Investasi Mahasiswa - Melita Indah Cahyani; Detak Prapanca; Sriyono sriyono (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to determine the factors that influence investment interest based on capital market training, risk perception, financial literacy, and minimum investment capital. This research method uses quantitative research. The population used is active students of S1 Management class 2018-2020 at Muhammadiyah Sidoarjo University. Non-probability sampling is Porposive sampling. This research collection technique uses a questionnaire or questionnaire. The data analysis technique uses PLS-SEM. The result of this study is that minimum investment capital has a significant positive effect on investment interest.